Verflixter Tom! und andere Geschwistergeschichten - Steinwart, Anne 1945- (Arena, 1995)
Short stories about sisters and brothers, and the good and bad of their relationships.
Keywords: Brothers and sisters -- Fiction; German language materials; Short stories, German; Geschwister; Anthologie; Kinderbuch